Aplicación de una auditoría tributaria en la cooperativa de Ahorro y Crédito Los Chasquis Pastocalle ltda., ubicada en la provincia de Cotopaxi, cantón Latacunga, parroquia Tanicuchi, al período de 01 de enero al 31 de diciembre del 2013 - Pila Vinocunga, Mónica Rocío (2015)
Acording work, development research it was able to establish a correct application of Tax Regulations that SRI provides to all taxpayers required to keep accounts. The main objective of this work is to verify compliance with tax obligations in accordance with the Internal Taxation Law provisions and its Implementing Regulations, to determine the correct handling given to taxes on fiscal year 2013 to avoid further sanctions, a report containing findings and recommendations on the performance of their tax obligations for appropriate decision-making issue, methods were used you also descriptive, analytical and research techniques such as surveys with its instrument the same questionnaire is directed to the administrative staff and customers of the auditee, Additional interview was applied to the manager and accountant of the financial institution, which allowed to obtain accurate information of the cooperative and it could find the following findings, there is not statements on time, because no one person is in charge of the tax area, there is no planning process of constant accounting for staff training in relation to the current tax aspect of the Internal Revenue Service (SRI).